Evaluation of the Efficacy of Different Serological Methods (rK39 dipstick, ELISA and IFA) Techniques in the Diagnosis of Visceral leishmaniasis. - S. Muosa, Israa; N. Younis, Nada; E. Jawad, Wasan (Iraqi Journal of Science, 2023)
The objective of this study was to compare the sensitivity and specificity of rK39,ELISA and IFA tests for the diagnosis of visceral leishmaniasis using bloodsamples. Samples were collected from 146 suspected patients and 30 healthyindividual as control. The results showed 52 (35.62%), 58 (39.73%) and 71(48.64%) positive samples by rK39, ELISA and IFA , respectively. IFA test showeda higher sensitivity (48.63%) than ELISA and rk39 dip stick (39.72%) and (35.61%)respectively. The highest sensitivity of agreement (K: 0.912) was found betweenrK39 dipstick and ELISA. Therefore, we suggest the application of rK39 dipstickand ELISA methods in endemic areas of visceral leishmaniasis for early andaccurate diagnosis of this disease